Optimizing Digital Literacy in Teaching Grammar through E-Portfolio at STKIP Lampung in Indonesia - Masitoh Oktavia; Januarius Mujiyanto; Hendi Pratama; Dwi Anggani Linggar Bharati (Universitas Negeri Semarang, 2021)
Using digital literacy in teaching Grammar courses by implementing an E-Portfolio meets the communicative purpose of language learning in a digital context. This study explains the idea of ​​assigning students to create an E-portfolio during learning grammar to assess the students' grammar understanding both in the grammar patterns as declarative knowledge and its application in writing as procedural knowledge. This study examines whether there is significance in students' achievement taught Grammar through integrating declarative and procedural knowledge by implementing E-Portfolio. The sample is forty Students for each group, taken from students of grammar class at English Department STKIP Lampung in Indonesia. This research employs an experimental design, the quantitative data taken from students' tests. The finding shows a significant difference in students' grammar understanding between experimental and control groups. The alternative hypothesis is accepted. It concluded that using Electronic Portfolio is positively practical to be implemented in Grammar courses that can integrate both declarative and procedural knowledge.